ABCE1 Regulates RNase L-Induced Autophagy during Viral Infections - Ramnani, Barkha (Viruses, 2021)
Host response to a viral infection includes the production of type I interferon (IFN) and the induction of interferon-stimulated genes that have broad antiviral effects. One of the key antiviral effectors is the IFN-inducible oligoadenylate synthetase/ribonuclease L (OAS/RNase L) pathway, which is activated by double-stranded RNA to synthesize unique oligoadenylates, 2-5A, to activate RNase L. RNase L exerts an antiviral effect by cleaving diverse RNA substrates, limiting viral replication; many viruses have evolved mechanisms to counteract the OAS/RNase L pathway. Here, we show that the ATP-binding cassette E1 (ABCE1) transporter, identified as an inhibitor of RNase L, regulates RNase L activity and RNase L-induced autophagy during viral infections. ABCE1 knockdown cells show increased RNase L activity when activated by 2-5A. Compared to parental cells, the autophagy-inducing activity of RNase L in ABCE1-depleted cells is enhanced with early onset. RNase L activation in ABCE1-depleted cells inhibits cellular proliferation and sensitizes cells to apoptosis. Increased activity of caspase-3 causes premature cleavage of autophagy protein, Beclin-1, promoting a switch from autophagy to apoptosis. ABCE1 regulates autophagy during EMCV infection, and enhanced autophagy in ABCE1 knockdown cells promotes EMCV replication. We identify ABCE1 as a host protein that inhibits the OAS/RNase L pathway by regulating RNase L activity, potentially affecting antiviral effects.